ANALISIS PENDAPATAN PEDAGANG MIKRO MAKANAN DAN MINUMAN DI SEKITAR MALL DINOYO CITY - Nisantoro, Wahyu Dwi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2016)
This study aimed to analyze the effect of variable capital , trading hours and locations micro traders to trade on the income of food and drinks around the Mall Dinoyo City Malang. In this study using primary data through direct interviews on 60 respondents micro traders of food and drinks around the Mall Dinoyo City with a list of questions that had been prepared . To achieve the goal, in this study using regression analysis ( OLS ). The results of this study indicate that the variable capital and trade locations positive and significant impact on the micro traders of food and drinks around the Mall Dinoyo . While variable trading hours do not significantly affect the income micro traders of food and drinks around the Mall Dinoyo City .